FORMATION OF MEDIA DIGITAL LITERACY OF PRIMARY SCHOOL STUDENTS - Avdarsol С.; Ongarbayeva А.Д. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
The article deals with the issues of media formation of digital literacy of primary school students. At the same time, media digital literacy refers to a person’s primary knowledge of modern information and the media world, the ability to work with various sources and types of information to solve specific tasks both in education and in professional activity, everyday life. The structures of media literacy and eight main categories are described: the use of information, relations in the media environment, creative use of media tools, ethics and values in the digital and media environment, security in the digital and media environment, law in the digital and media environment, economic aspects of media activity. Within the framework of these categories, the content of the training of primary school students, methodological techniques used in primary classes to ensure the achievement of the planned results in the field of media education are reflected.